Analysis of Work Discipline and Satisfaction with Employee Performance at PT Kamaraya Land Semarang - Sutaat, Sutaat; Purwaningrum, Dyah (ProBisnis : Jurnal Manajemen, 2024)
This study examined the effect of work discipline on employee performance and satisfaction with employee performance at PT Kamaraya Land Semarang. The research design used is an explanatory study in order to understand a phenomenon to be researched, and the population and sample in this research are all employees of PT Kamaraya Land Semarang, totaling 45 respondents using a questionnaire for collection, which was processed using SPSS 21.00 for windows. Discipline has a negative effect on the performance of PT Kamaraya Land Semarang employees and job satisfaction has a positive effect on the performance of PT Kamaraya Land Semarang employees.